AB0622 Heart conduction disturbances in patients treated with antimalarials. (23rd January 2014) - Pérez-Martín, I.; Bejerano, C.; Peirό, E.; Blanco, R.; Agudo, M.; Martínez-Taboada, V.M.; González-Gay, M.A.
Abstract : Background: Chloroquine and Hydroxichloroquine are well-known anti-malarial drugs used in the management of several rheumatologic diseases, in particular in patients with Systemic Lupus Erythematosus (SLE) and Rheumatoid Arthritis (RA). Apart from the ophthalmologic complication, these drugs are considered to be relatively safe drugs. However, their prolonged use may be associated with other complications, including heart rhythm problems such as heart block. Methods: We reviewed the medical records of a series of patients seen at the outpatient Rheumatology Clinic of a University Hospital, who required prolonged anti-malarial drug therapy. In the present study we aimed to identify the alterations in the heart conduction system as well as the conditions associated to these abnormalities. Results: From a series of 212 patients treated with antimalarials, 154 (72.64%) were diagnosed with RA, 57 (26.88%) with SLE and 1 with Still disease. We disclosed 9 patients (6 females/3 males) who experienced heart conduction disturbances. The mean age at time of the diagnosis of the cardiac conduction disturbances was 61.3±17.2 years (range 20-81). The mean duration of the disease before the onset of these heart complications was 90±52 (18- 204) months. SLE was the disease more frequently associated with these complications (5 patients) followed by RA (3 cases) and Still disease (1 case). Two of 9 who suffered the heart complication had abnormal kidney function with a clearance ≤40mg/dl. Chloroquine and hydroxichloroquine were administrated in a single dose of 250 mg/daily and 200 mg/twice daily respectively. The mean weight of the patients was 66, 33 kg ± 7, 28 (51-75).The weight-adjusted dose for the chloroquine were 3.87±0.5 mg/kg (3.47-4.9) and 5.9±0.55 (5.3-6.3) for the hydroxichloroquine. Before the onset of antimalarial therapy only 2 of the patients had abnormal ECG (atrial fibrillation (AF) and right bundle-branch block respectively). Following anti-malarial drug therapy the following heart conduction disturbances were observed: 5 atrioventricular blocks (2 associated with right bundle-branch block and other one with left bundle-branch), 2 right bundle-branch block, 1 left bundle-branch block, 1 blocked AF associated with right bundle-branch. Seven of these patients required pacemaker. Conclusions: We must be aware of the potential risk of having heart conduction disturbances following prolonged used of anti-malarial drugs. Disclosure of Interest: None Declared